2010
DOI: 10.1021/ja9086374
|View full text |Cite
|
Sign up to set email alerts
|

Cyclobutanone Analogues of β-Lactams Revisited: Insights into Conformational Requirements for Inhibition of Serine- and Metallo-β-Lactamases

Abstract: The most important mode of bacterial resistance to beta-lactam antibiotics is the expression of beta-lactamases. New cyclobutanone analogues of penams and penems have been prepared and evaluated for inhibition of class A, B, C, and D beta-lactamases. Inhibitors which favor conformations in which the C4 carboxylate is equatorial were found to be more potent than those in which the carboxylate is axial, and molecular modeling studies with enzyme-inhibitor complexes indicate that an equatorial orientation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 36 publications
(18 reference statements)
1
64
0
Order By: Relevance
“…Cyclobutanones have previously been explored as reversible ␤-lactamase inhibitors with modest, but broad-spectrum ␤-lactamase inhibition. Cyclobutanones also exhibit covalent binding as the hemiketal to the active-site serine of serine hydrolases as seen crystallographically (56). The three different isomers of a mechanistic cyclobutanone ligand (Scheme 1) were screened for relative activity against FTT258 before attempting co-crystallization.…”
Section: Figure 1 Ftt258 Substrates and Ligandmentioning
confidence: 99%
“…Cyclobutanones have previously been explored as reversible ␤-lactamase inhibitors with modest, but broad-spectrum ␤-lactamase inhibition. Cyclobutanones also exhibit covalent binding as the hemiketal to the active-site serine of serine hydrolases as seen crystallographically (56). The three different isomers of a mechanistic cyclobutanone ligand (Scheme 1) were screened for relative activity against FTT258 before attempting co-crystallization.…”
Section: Figure 1 Ftt258 Substrates and Ligandmentioning
confidence: 99%
“…General formula for compounds [6][7][8] 3e displayed notable inhibitory activity on VIM-2 isoform (K i of 15 and 6 mM, respectively). Conversely, aldehyde 2e was characterized by a comparable inhibitory profile toward both VIM-2 and NDM-1 (K i ¼ 10 mM).…”
Section: Zinc-interacting Groupsmentioning
confidence: 99%
“…Therefore, facing the mounting threat of antimicrobial resistance today represents a great challenge for clinicians and medicinal chemists. One important mechanism of resistance to b-lactams 5 is the production of one or more b-lactamase(s), which efficiently inactivate these antibiotics 6,7 . The global spread of extended-spectrum b-lactamases (ESBLs) led to increased use of carbapenems, broad-spectrum antibiotics which are stable to ESBLs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have found that cyclobutanone analogues of the penems and penams inhibit both SBLs and MBLs 8a. We identified the cyclobutanone penem analogue 1 (Figure 1) to be the most potent compound tested against class A and C SBLs, and to have modest inhibition of the IMP‐1 MBL 8a. However, although we obtained crystallographic evidence for SBL inhibition, involving binding of the cyclobutanone by a hemiketal to the nucleophilic serine,8a no information has been available on how cyclobutanones inhibit MBLs.…”
mentioning
confidence: 99%
“…Our results, however, show that the SPM‐1 active site can bind with reasonable affinity to a species (i.e., a hydrated cyclobutanone) whose tetrahedral carbon (C6) atoms render it closely (though not perfectly) analogous to the oxyanion intermediate. Taking into consideration the activity of cyclobutanones and boronates against all classes of SBLs,8a, 17 these results indicate that structures mimicking the tetrahedral oxyanion merit investigation as starting points for potent inhibitors that are hydrolytically stable and effective against both SBLs and MBLs.…”
mentioning
confidence: 99%